2020
DOI: 10.1038/s41598-020-67432-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of polyamine biosynthetic pathways in skin lesions and in plasma reveals distinct profiles in diffuse cutaneous leishmaniasis

Abstract: to be linked to the parasite load in lesion sites 3. In MCL lesions, parasites are rarely detected whereas in DCL lesions heavily parasitized macrophages are usually observed 2. We have previously shown high concentrations of arginase-1 (ARG1), ornithine decarboxylase (ODC), prostaglandin E2 (PGE2) and transforming growth factor β (TGF-β) in DCL patients 4 , which could contribute to an ineffective immune response unable to hamper parasite replication. Although recent studies have shown that components of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
1
14
0
1
Order By: Relevance
“…Clinical data of diffused cutaneous leishmaniasis (DCL) showed that patients present higher ornithine, spermidine, and citrulline in plasma samples than mucocutaneous leishmaniasis (MCL), using HPLC tool [49]. Indeed, DCL skin biopsies upregulated arginase 1 (ARG1) and spermine synthase mRNAs involved in polyamines biosynthesis concerning localized cutaneous leishmaniasis (LC) and MCL lesions, highlighting the significance of host ARG1 and arginine transporter (cationic amino acid transporter, CAT2) in MCL [49]. However, the ARG1 and arginase 2 (ARG2) transcripts are lower in DCL than healthy controls [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data of diffused cutaneous leishmaniasis (DCL) showed that patients present higher ornithine, spermidine, and citrulline in plasma samples than mucocutaneous leishmaniasis (MCL), using HPLC tool [49]. Indeed, DCL skin biopsies upregulated arginase 1 (ARG1) and spermine synthase mRNAs involved in polyamines biosynthesis concerning localized cutaneous leishmaniasis (LC) and MCL lesions, highlighting the significance of host ARG1 and arginine transporter (cationic amino acid transporter, CAT2) in MCL [49]. However, the ARG1 and arginase 2 (ARG2) transcripts are lower in DCL than healthy controls [49].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DCL skin biopsies upregulated arginase 1 (ARG1) and spermine synthase mRNAs involved in polyamines biosynthesis concerning localized cutaneous leishmaniasis (LC) and MCL lesions, highlighting the significance of host ARG1 and arginine transporter (cationic amino acid transporter, CAT2) in MCL [49]. However, the ARG1 and arginase 2 (ARG2) transcripts are lower in DCL than healthy controls [49]. L. amazonensis infection of BALB/c-macrophages increases host Cat2 and Arg1 transcripts, parasite arginine transporter (amino acid permease 3, AAP3), and parasite arginase [23].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that l -arginine is preferentially metabolized for the biosynthesis of polyamine pathway intermediates as opposed to the biosynthesis of NO biosynthetic pathway intermediates ( Figure 1c ). 33 , 34 Furthermore, we found no significant differences in the concentration of citrulline, a precursor of l- arginine, between HCs and NTM-PD patients, although a minor but significant increase in arginino-succinate was detected in patients with Mabc infection compared to HCs ( Figure 1b ). These data suggest that l- arginine depletion is a result of rapid consumption rather than reduced biosynthesis.…”
Section: Resultsmentioning
confidence: 74%
“…Recently, Malta-Santos et al (2020) investigated the importance of the polyamine biosynthetic pathway in CL lesions. Diffuse CL was associated with higher concentrations of amino acids, polyamines and its substrate transporters compared to MCL or localized CL.…”
Section: Assessment Of Metabolic Pathwaysmentioning
confidence: 99%
“…The most upregulated transcripts in diffuse CL lesions were CAT2A (isoform encoded by SLC7A2), ARG1 and SMS compared to MCL lesions acting in the regulation of arginine availability. A differential gene expression of polyamine metabolism-related genes of patients’ lesions was associated with parasite loads and the leishmaniasis disease outcome ( Malta-Santos et al, 2020 ).…”
Section: Assessment Of Metabolic Pathwaysmentioning
confidence: 99%